2022
DOI: 10.1038/s41467-022-27984-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar connectivity maps embody individual adaptive behavior in mice

Abstract: The cerebellar cortex encodes sensorimotor adaptation during skilled locomotor behaviors, however the precise relationship between synaptic connectivity and behavior is unclear. We studied synaptic connectivity between granule cells (GCs) and Purkinje cells (PCs) in murine acute cerebellar slices using photostimulation of caged glutamate combined with patch-clamp in developing or after mice adapted to different locomotor contexts. By translating individual maps into graph network entities, we found that synapt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 89 publications
2
10
0
Order By: Relevance
“…Therefore, we suggest that similar rules may apply in the cerebellar GC-MLI-PC FFI pathway and individual GC clusters might be selected by PCs to ensure proper E/I balance in PCs. These findings are in agreement with the spatial organization of the GC-PC connectivity maps that correlate with specific locomotor context at the level of individuals (Spaeth et al, 2022). FFI circuits similar to the GC-MLI-PC with synapses that show STD are ubiquitous in the brain.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, we suggest that similar rules may apply in the cerebellar GC-MLI-PC FFI pathway and individual GC clusters might be selected by PCs to ensure proper E/I balance in PCs. These findings are in agreement with the spatial organization of the GC-PC connectivity maps that correlate with specific locomotor context at the level of individuals (Spaeth et al, 2022). FFI circuits similar to the GC-MLI-PC with synapses that show STD are ubiquitous in the brain.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, this behavior mimics physiological properties as incoming action potentials from the pre-cerebellar nuclei likely invade all the MF collaterals in the cerebellum. Anatomical reconstructions showed that a single MF gives rise to many distant rosettes in a cerebellar lobule (Shinoda et al, 2000;Sultan, 2001;Quy et al, 2011;Na et al, 2019), activating discrete and distinct GC clusters that may target the same PCs as shown previously (Valera et al, 2016;Spaeth et al, 2022). This latter configuration is also mimicked by the surface illumination used in our experiments which showed similar results than single rosette excitation but with a wider range of ΔLat.…”
Section: Single or Surface Illumination Evoked Temporal E/i Decorrela...supporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, many pre-cerebellar nuclei carrying distinct modalities project MFs to the GC layer of the same microzone 27, 11. In the anterior lobe, for example, lobule IV and V receive MFs from the spinocerebellar tract (e.g., DSCT, dorsal spinocerebellar tract) and the external cuneate conveying proprioceptive information from the hindlimbs and the forelimbs, respectively, as well [24] as from the pontine nuclei, which carry information from the cerebral cortex such as motor plans and motor commands [28]. Therefore, individual GCs can integrate multimodal information [26,29] but see [30] that combine both motor plans or commands and sensory feedback.…”
Section: The Mossy Fiber To Purkinje Cell Pathway: An Anatomy Favorin...mentioning
confidence: 99%